FUNGSI LABORATORIUM FORENSIK DALAM PEMBUKTIAN TINDAK PIDANA NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 - I Putu Wisnu Nugraha; Anak Agung Putu Wiwik Sugiantari (Jurnal Hukum Saraswati (JHS), 2022)
Misuse of Narcotics and Psychotropics can be categorized as a crime without victims or (Crime Without Victim) is a crime that does not cause suffering to victims of other people's criminal acts. Actually the use of Narcotics and Psychotropics itself is very necessary for medical purposes. So that the use is unattended and dependent for its users. The Forensic Laboratory as a special police tool has the task of assisting the police of the Republic of Indonesia, assisting in evidence to reveal everything related to all kinds and kinds of Narcotics and Psychotropics, who are the users and who are the dealers. The problems that will be discussed in the thesis are how the duties and functions of the forensic laboratory are in an effort to prove evidence against criminal acts of narcotics and psychotropic abuse and what are the factors that can be an obstacle for the forensic laboratory in an effort to uncover criminal acts of narcotics and psychotropics. The method used in writing is the normative legal research method, namely research conducted by examining library materials or primary legal materials and secondary legal materials. The results of the study show that the Forensic Laboratory was established to assist in finding and collecting evidence in the investigation process as stated in Article 7 paragraph (1) letter of Law Number 8 of 1981 concerning Criminal Procedure Code (KUHAP) which states that bringing in the necessary experts in in relation to the examination of cases and Article 120 paragraph (1) of the Criminal Procedure Code states that if the investigator deems it necessary, he or she may ask for the opinion of an expert or a person with special expertise. The Forensic Laboratory also has the task of examining Narcotics and Psychotropics and in proving it, evidence is needed to be used for investigation purposes. Inhibiting factors can occur in carrying out proof of evidence so that efforts to overcome obstacles to forensic laboratory examinations need to be implemented, so that by implementing efforts to overcome obstacles can facilitate forensic laboratories in carrying out their duties and functions.